Rudimentary sympathy in preverbal infants: preference for others in distress. - Yasuhiro Kanakogi; Yuko Okumura; Yasuyuki Inoue; Michiteru Kitazaki; Shoji Itakura (PLoS ONE, 2013)
Despite its essential role in human coexistence, the developmental origins and progression of sympathy in infancy are not yet fully understood. We show that preverbal 10-month-olds manifest sympathetic responses, evinced in their preference for attacked others according to their evaluations of the respective roles of victim, aggressor, and neutral party. In Experiment 1, infants viewing an aggressive social interaction between a victim and an aggressor exhibited preference for the victim. In Experiment 2, when comparing the victim and the aggressor to a neutral object, infants preferred the victim and avoided the aggressor. These findings indicate that 10-month-olds not only evaluate the roles of victims and aggressors in interactions but also show rudimentary sympathy toward others in distress based on that evaluation. This simple preference may function as a foundation for full-fledged sympathetic behavior later on.